Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Terhadap Kinerja Guru dan Implikasinya Pada Prestasi Lulusan - Iyus Rustandi (Universitas Mathla'ul Anwar Banten, 2019)
The purpose of this research is to get empirical evidence about the influence of principal’s leadership and teacher’s motivation toward teacher’s performance and the achievement of graduates in Hospitality Major of Vocational High School At Kabupatan Bandung. The result are expected to contribute in the development of management science specially in education management. For identical schools and practitioners, the result of this study are expected to provide useful information about the importance in order to improve the achievement of graduates.This research was conducted in Hospitality Major of Vocational High School At Kabupatan Bandung. The research method uses survey method with quantitative research approach. On the other hand, type of this research is descriptive and verificative. To test the hypothesis of the study, we used statistical methods of path analysis.According to the test result we found significant influence between principal’s leadership against teacher’s performance with total effect of 9,90 %, a significant influence between teacher’s motivation against the performance of teacher with percentage of 50,53%, significant influence between proncipal leadership and teacher’s motivation against the performance of teachers with percentage of 60,43 %, the performance of teachers giving contribution to the achievement of graduates trhough the teacher’s performance with a total effect of 68,89 %.